2022
DOI: 10.3389/fneur.2022.872664
|View full text |Cite
|
Sign up to set email alerts
|

MRI appearance of chronic subdural hematoma

Abstract: ObjectiveWe aimed to describe the magnetic resonance imaging (MRI) characteristics of chronic subdural hematoma (cSDH) and to ascribe MRI patterns.MethodsA total of 20 patients having 27 subdural hematomas underwent contrast-enhanced (CE) MRI of the brain at our institution between April 2019 and May 2021. The images were independently evaluated by two experienced neuroradiologists with regard to imaging characteristics on T1w, T2w, T2*-GRE, FLAIR, diffusion-weighted magnetic resonance imaging (DWI), and CE im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The following initial CT findings were investigated: initial maximal thickness of subdural hematoma, density type of CSH, location of CSH (bilateral, left, or right), and distance of midline shifting. Density type of CSH was categorized into the following 4 types: homogeneous hypodensity ( < 25 Housefield unit [HU]), homogeneous isodensity (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), mixed type, and layered type on CT findings (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following initial CT findings were investigated: initial maximal thickness of subdural hematoma, density type of CSH, location of CSH (bilateral, left, or right), and distance of midline shifting. Density type of CSH was categorized into the following 4 types: homogeneous hypodensity ( < 25 Housefield unit [HU]), homogeneous isodensity (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), mixed type, and layered type on CT findings (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, other studies have shown that the presence of brain atrophy is associated with recurrence because of the presence of a persistent subdural space [15,30]. Furthermore, if there is septation in radiologic findings, recurrence may be caused by a residual hematoma because it is difficult to drain the hematoma completely [29,31,32]. Also, if there is a residual hematoma, a neovascularized membrane develops, and therefore, continuous microbleeding in fragile and leaky vessels can occur, which can lead to hematoma accumulation.…”
Section: Recurrence Of Cshmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) may provide helpful information for diagnosing multiseptated CSDH. 2) Lee et al 4) reported that diffusion-weighted MRI provides better resolution of multiseptated CSDH and can predict post-treatment failure more accurately than brain CT.…”
mentioning
confidence: 99%